Kepemimpinan dan Kompensasi terhadap Kinerja Pegawai Nonmedis Rumah Sakit - Fitria Fitria; Suyadi Suyadi; Hery Hery (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of leadership, compensation, and the two factors (leadership and compensation) on the performance of non-medical employees of Dr. Hospital. Sobirin, Musi Rawas Regency. The research method used is a quantitative method. Data collection methods in the form of observation, questionnaires, and documentation. The results showed that the results of the T test on the leadership variable showed the tcount value was greater than ttable, namely 1.933 > 0.679 with dk = 60 (60-3) and the significant level was 0.058. The compensation variable shows the value of tcount is greater than ttable, namely 3.373 > 0.679 with dk = 60 (60-3) and the significant level of sig is 0.001. The fcount value of = 9.117 is greater than the ftable value = 3.17 and the probability (sig. 0.004). In conclusion, partially leadership and compensation variables, and simultaneously leadership and compensation variables have a partial and significant effect on the performance of non-medical employees at Dr. Hospital. Sobirin, Musi Rawas Regency. Keywords: Leadership, Employee Performance, Compensation